2017
DOI: 10.1016/s0960-9776(17)30290-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between body mass index and hormone-receptor status as a prognostic factor in lymph-node-positive breast cancer

Abstract: The aim of this study was to determine the relationship between the body mass index (BMI) at a breast cancer diagnosis and various factors including the hormone-receptor, menopause, and lymph-node status, and identify if there is a specific patient subgroup for which the BMI has an effect on the breast cancer prognosis. We retrospectively analyzed the data of 8,742 patients with non-metastatic invasive breast cancer from the research database of Asan Medical Center. The overall survival (OS) and breast-cancer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…In the course of some malignancies a paradoxical phenomenon has been observed, indicating that obesity may be an oncogenic factor and -at the same time -may constitute a favorable prognostic factor (4,5). The dual and opposite influence of obesity on the course of the same disease has been called the obesity paradox and has been described in some chronic diseases, including cardiovascular (6) and cerebrovascular diseases (7).…”
mentioning
confidence: 99%
“…In the course of some malignancies a paradoxical phenomenon has been observed, indicating that obesity may be an oncogenic factor and -at the same time -may constitute a favorable prognostic factor (4,5). The dual and opposite influence of obesity on the course of the same disease has been called the obesity paradox and has been described in some chronic diseases, including cardiovascular (6) and cerebrovascular diseases (7).…”
mentioning
confidence: 99%
“…5,8,10 Chung et al, for example, in a study of 8742 patients found a significant difference in mean tumor size among underweight, normal weight, overweight, and obese patients (1.96 cm vs 2.29 cm vs 2.54 cm vs 2.64 cm, respectively, P < .001). 8 They, however, did not control for potential covariates. Haakinson et al similarly found in their study of 1352 invasive breast cancer patients that obese patients had a larger mean tumor size than those who were nonobese (2.0 cm vs 1.6 cm, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown similar results. 5,8,10 Chung et al, for example, in a study of 8742 patients found a significant difference in mean tumor size among underweight, normal weight, overweight, and obese patients (1.96 cm vs 2.29 cm vs 2.54 cm vs 2.64 cm, respectively, P < .001). 8 They, however, did not control for potential covariates.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations